ВИЗАНТИЙСКИЕ ИСТОКИ РУССКОЙ ДУХОВНОСТИ (Филолошки студии, 2019)
The article investigates into the problem of Byzantine culture influence which is attempted to be traced in the formation of Russian culture and literature. In the article there are considered the attitudes towards Byzantine culture on the part of the 19th century Russian culture various trends representatives (such as ‘the westernizers’ and ‘the Slavophiles’); there are also exposed both the genetic ties of Russian culture with Byzantine aesthetic ideas and those of Byzantine version of Christianity with the bunch of Russian classical literature ideas (for example, of such writers as A. Pushkin, N. Gogol, F. Dostoyevsky, N. Leskov, L. Tolstoy, etc). As the result of the study the author comes to the conclusion which could be worded as follows. The question of the ‘Byzantine heritage’ significance for the development of a certain national culture used to be topicalised in the transitional, crisis periods of national histories when the problem as to what further historical way for the nation to choose sprang up.